2019
DOI: 10.1002/smll.201903818
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Regulated Smectic Emulsion with Switchable Lasing Application

Abstract: be a two-step process, since the separated liquids need specific mechanical treatments such as sonication or gas bubbling to return to the initial emulsion form, [8,9] restricting the practical applications. Moreover, the switchable emulsifiers need to be specially designed according to the physical and chemical properties of the host/guest liquids and switching triggers, which makes this method complicated, time consuming, and expensive. Finally, although it has been demonstrated that self-emulsification meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Kim et al 44 observed a phase transition when LC molecules containing perfluoroalkyl groups formed an emulsion in silicone oil (Figure 6a). When the LC molecules are cooled in an isotropic liquid state and transition to a smectic state, they form spherical and myelin‐like structures.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kim et al 44 observed a phase transition when LC molecules containing perfluoroalkyl groups formed an emulsion in silicone oil (Figure 6a). When the LC molecules are cooled in an isotropic liquid state and transition to a smectic state, they form spherical and myelin‐like structures.…”
Section: Applicationsmentioning
confidence: 99%
“…(a) The LC dispersed in the silicone oil undergoes a phase change and spontaneously forms a myelin structure. (scale bars = 20 μm) 44,74 . (b) FF‐SEM and x‐ray diffraction analysis of fracture plane for Q 230 cubic phase of lipid‐water system (scale bar = 200 nm) 45 .…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the unique features, LCs have been extensively used in biosensing, temperature detection, and whispering‐gallery mode (WGM) laser resonators. [ 19–24 ] As the chiral dopant increases in CLC droplets, the number of periodic refractive index variation (periodic shells) increases to form higher structural confinement and chirality. Recent studies have further applied CLC microdroplets to obtain spherical or lateral confinement of optical modes.…”
Section: Figurementioning
confidence: 99%
“…Switchable interfaces have offered tremendous opportunities over the past decade, including bioelectronics, optical devices, ,, laser switches, biomedical sensors, , and fundamental biology. In particular, the concept of “switchable biointerfaces” can be referred to as interfaces that change their microscopic properties in response to biological stimuli or biomolecular interactions. Contrary to artificially designed interfaces, switchable biointerfaces that take advantage of a biological system and biorecognition have demonstrated high functionality far beyond that obtained from nanomaterials. Among all biomolecules, DNA is one of the most potent biomaterials known for its controllable synthesis and specificity of base-pair interactions. Besides biomedical applications, the programmability and self-assembly of DNA structures offer versatile ways to construct DNA biointerfaces and tailor optical responses. The stimuli-responsive properties of DNA molecules thus enable the development of program-switchable DNA interfaces. , …”
Section: Introductionmentioning
confidence: 99%